LINE FOLLOWER BASED CONTAINER ROBOT AS A SOLUTION TO IMPROVE SERVICE MOBILITY IN UNIVERSITAS TANJUNGPURA - Hartono, Budi; Hadary, Ferry; Putri, Eka Ardiani (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2023)
The design and method for this prototype project utilize an IDE, which is defining, developing, and evaluating. The definition utilize ATMEGA 328p controller that acts as the brain of the robot. The robot uses a 2.6Ah li-ion battery with power consumption load of approximately 1.37Wh/meter without any load in the container. It employs a binocular spring beam HX711 sensor with an accuracy 99.08% to measure the weight of the container being carried. Additionally, TCRT5000 sensor with 100% accuracy is used to detect the line. RFID-RC522 sensor with an accuracy 96.43% and distance less than 6cm between cards utilized on warehouse or pharmacy addressing. HC-SR04 sensor with an accuracy 99.25% employed to detect objects in the robot's vicinity. The robot powered by DC motors controlled with driver. The development stage involves constructing the framework, sensor circuitry, and track layout on the robot, which simulates the Universitas Tanjungpura Hospital using 1:70 scale model. The evaluation is conducted to ensure that each component of the robot functions properly. Based on the results, it can be concluded that this automated cargo-carrying container robot prototype, with a reliability level of 98.84%, can be implemented in hospitals to transport goods and facilitate repetitive tasks.